DETERMINAN PARTISIPASI DAN PERAN PETANI MUDA DALAM PENGEMBANGAN PERTANIAN RAMAH LINGKUNGAN DI DESA CISONDARI, KECAMATAN CIWIDEY, KABUPATEN BANDUNG, JAWA BARAT - Fitrah Rahmah Insani; Iwan Setiawan; Siska Rasiska (Universitas Galuh Ciamis, 2018)
Agricultural development since the last two decades has been mainstreamed to a more environmentally friendly perspective. Cisondari is a village known for applying environmentally friendly practices in their agriculture. In this globalization era, urbanization is inevitable, especially for rural youths. This situation has impacted agricultural workforce structure in the rural area, threatening its future agriculture. However, Cisondari shows an anomaly condition. Cisondari’s agricultural development is highly influenced by the active presence of rural youths. This study aims to identify the determinants of the rural youths’ participation in Cisondari’s agricultural development. The study applies quantitative methods through descriptive statistics analysis. Data were gathered by structured interviews to respondents selected by simple random sampling technique. The results show that the determinants of youths staying in the village are motivation, innovation, and environmental factors. The young farmers are involved in environmentally friendly agricultural practices in many phases ranged from planning, conducting, monitoring, to evaluation. Keywords: Eco-friendly Farming, Youth Participation, Farmers Regeneration